2017
DOI: 10.1177/0884533617719669
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Screening vs Nutrition Assessment: What’s the Difference?

Abstract: Screening and assessment imply different processes, with the former indicating risk factors for a deprived nutrition condition and the latter providing the nutrition diagnosis. Both should be routinely performed at hospital admission according to recommended guidelines; however, this is not the reality worldwide, and undernutrition remains highly prevalent in the hospital setting. Therefore, the objective of the current review is to delve into the principles leading to nutrition status deficiencies and how the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
61
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 119 publications
1
61
1
1
Order By: Relevance
“…As discussed previously, nutrition screening determines the nutrition risk of a patient, and in this context, the risk of acquiring complications as a consequence of failure of optimal nutrition provision. In contrast, nutrition assessment is a formal evaluation of patient nutrition status by a trained healthcare professional, usually a dietitian, and results in a nutrition‐related diagnosis …”
Section: Nutrition Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…As discussed previously, nutrition screening determines the nutrition risk of a patient, and in this context, the risk of acquiring complications as a consequence of failure of optimal nutrition provision. In contrast, nutrition assessment is a formal evaluation of patient nutrition status by a trained healthcare professional, usually a dietitian, and results in a nutrition‐related diagnosis …”
Section: Nutrition Assessmentmentioning
confidence: 99%
“…Critically ill patients are often unconscious and therefore weight and food history are either not available or obtained from family member . Although 1 feasibility study reported that weight and food history can be obtained in 54.5% and 76.4% of the ICU patients, respectively, the accuracy of the information provided (especially by proxy) may not be verifiable. Required subjective clinical interpretation and therefore training is needed especially among nonexperts …”
Section: Nutrition Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…I read with great interest the letter to the editor about my authored review article on nutrition screening vs nutrition assessment . I agree with the arguments by Matarese and Charney because I am also a defender of the Subjective Global Assessment (SGA) tool despite its “subjectivity,” which I acknowledge to rely entirely on clinical reasoning, hindering its obligation to be carried out by well‐trained professionals.…”
mentioning
confidence: 76%
“…We read with interest the article titled “Nutrition Screening vs Nutrition Assessment” by Dr. Correia . Similar articles were previously published by Charney as well as an evaluation of validated screening tools by Anthony …”
mentioning
confidence: 95%